2020
DOI: 10.21203/rs.3.rs-26812/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial Activity Screening of Rhizosphere Soil Bacteria from Tomato and Genome-Based Analysis of their Antimicrobial Biosynthetic Potential

Abstract: Background: Tomato plant growth is frequently hampered by a high susceptibility to pests and diseases. Traditional chemical control causes a serious impact on both the environment and human health. Therefore, seeking environment-friendly and cost-effective green methods in agricultural production becomes crucial nowadays. Plant Growth Promoting Rhizobacteria (PGPR) can promote plant growth through biological activity. Their use is considered to be a promising sustainable approach for crop growth. Moreover, a v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…1 ). An important biocontrol mechanism of biological control agents (BCAs) involves the secretion of antibacterial substances and inhibition of pathogen growth (Zhou et al ., 2021 ). Among the top 10 bacterial species listed based on their scientific and economic importance in plant diseases, Pseudomonas syringae pathovars and Ralstonia solanacearum were ranked as the first and second most important bacterial pathogens respectively (Mansfield et al ., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). An important biocontrol mechanism of biological control agents (BCAs) involves the secretion of antibacterial substances and inhibition of pathogen growth (Zhou et al ., 2021 ). Among the top 10 bacterial species listed based on their scientific and economic importance in plant diseases, Pseudomonas syringae pathovars and Ralstonia solanacearum were ranked as the first and second most important bacterial pathogens respectively (Mansfield et al ., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found, where a total of 180 strains of Bacillus were isolated from the tomato rhizosphere and these strains were tested against Pseudomonas syringae , Phytophthora infestans , Verticillium dahliae , Erwinia carotovora and Botrytis cinerea . Moreover, 34 Bacillus strains were found to have the best antagonistic activity against these plant pathogens with the production of surfactin, subtilin fengycin and bacillibactin compounds [ 82 ]. Ramesh and Phadke (2012) carried out a similar study in which they isolated 109 strains of endophytic rhizobacteria from eggplants and assessed their biocontrol efficiency against R. solanacearum [ 16 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…5B). Similarly, Zhou L et al found the great number of varieties of BGCs in Paenibacillus and Bacillus strains by genome mining [25].…”
Section: Genome Mining For Bgcs Of Antimicrobial Compoundsmentioning
confidence: 97%